CRITICAL PEDAGOGY IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 TO IMPROVE DIGITAL LITERACY STUDENTS WELCOMING SOCIETY 5.0 IN INDONESIA - Setiawardani, Wawan; Robandi, Babang; Djohar, As'ari (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2021)
Society 5.0 is a condition of society that is integrated with technology. This is closely related to the 4.0 industrial revolution which is also known as the disruption era. This reality is both a challenge and an opportunity for educators as part of society 5.0 in improving the quality of education as a vehicle for building a critical, cultured, creative, and futuristic generation. Based on these thoughts, the long-term objective of this study is to build futuristic pedagogical competencies. The specific target of this research is to find a pedagogical best practice to increase students' digital literacy in the digital era in welcoming society 5.0 in Indonesia. The research model used in this study is a mixed-methods research model. The sample of this research is students of the University of Pendidikan Indonesia in the semester I with 25 respondents. The research instrument was the test material (pretest-posttest) and semi-structured interview guidelines. From the data analyzed, that the significant value of 0.000 <0.050 (H0 is rejected). This shows that the mean pretest score is significantly smaller than the average posttest score. In line with this, the results of the interviews show that students are more careful with information obtained from the internet after treatment in learning. In other words, the application of a critical pedagogic model has an impact on improving students' digital literacy.